2022
DOI: 10.3390/polym14091817
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Pro-Regenerative Effects of Hyaluronan-Chitlac Mixture in Human Dermal Fibroblasts: A Skin Ageing Perspective

Abstract: Inflammation and the accumulation of reactive oxygen species (ROS) play an important role in the structural and functional modifications leading to skin ageing. The reduction of inflammation, cellular oxidation and dermal extracellular matrix (ECM) alterations may prevent the ageing process. The aim of this study is to investigate the expression of pro-inflammatory markers and ECM molecules in human dermal fibroblasts derived from young and middle-aged women and the effects of lactose-modified chitosan (Chitla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In particular, Gal-3 was recently associated with inflammation and ECM degradation in COPD [ 10 , 41 ]. Moreover, we recently demonstrated that the combination of HA and lactose-modified chitosan can prolong and improve the well-known anti-inflammatory activity of HA, attenuating macrophage-induced inflammation, MMP expression, and ROS production [ 17 , 42 ]. Macrophages are crucial regulatory cells of host defense and macrophage-induced inflammation contributes to the injury of bronchial tissues [ 4 , 10 , 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Gal-3 was recently associated with inflammation and ECM degradation in COPD [ 10 , 41 ]. Moreover, we recently demonstrated that the combination of HA and lactose-modified chitosan can prolong and improve the well-known anti-inflammatory activity of HA, attenuating macrophage-induced inflammation, MMP expression, and ROS production [ 17 , 42 ]. Macrophages are crucial regulatory cells of host defense and macrophage-induced inflammation contributes to the injury of bronchial tissues [ 4 , 10 , 12 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bioactive properties of CTL and its ability to induce cell aggregation , have been widely reported in the literature, both in vitro and in vivo . ,,,,, …”
Section: Discussionmentioning
confidence: 99%
“…In this way, the expression of Gal-1-regulated genes is reduced, leading to a decrease in inflammation . Since CTL has been demonstrated to be able to inhibit the expression of galectin proteins both in vivo and in vitro , ,,, there is a growing interest in the use of this polymer for the production of materials to be used in the field of cartilage regeneration. , …”
Section: Introductionmentioning
confidence: 99%
“…25 This allows the formation of an ammonium salt of DMTMM which reacts, by a substitution mechanism, with the carboxylic group of HA to form the active triazine-ester followed by a nucleophilic attack of LAC-NH 2 . 7 To synthesize samples with different DS values in a range considered ideal according to previous biological evaluation, 8 various reaction parameters, such as stoichiometry of the triazine condenser (DMTMM) and LAC-NH 2, and pH, were optimized.…”
Section: Hylach ® Synthesismentioning
confidence: 99%
“…Interaction studies were performed on saccharide ligands and OHA and HYLACH ® (OHY1 and OHY2), obtained by enzymatical hydrolysis. OHY1 and OHY2 were selected due to the similarity of molecular weight and DS with HYLACH 1 and HYLACH 3, respectively, cited by Donato et al 8 ITC results showed that the interactions between Gal-3 and saccharide ligands, OHA and OHY are all energetically favorable binding reactions (ΔG negative) and entropically driven (TΔS > 0), except for OHY2. For small ligands (LAC-NH 2 , galactose, and lactose) the stoichiometry of the interaction (N) is in the order of 1 protein:1 ligand, and the dissociation constant (K D ) is the order of µM, with values similar to data reported for lactose.…”
Section: Isothermal Titration Microcalorimetrymentioning
confidence: 99%